2021
DOI: 10.34257/gjmrfvol21is7pg1
|View full text |Cite
|
Sign up to set email alerts
|

Usage of E-Polytetrafluoroethylene (e-PTFE) Membrane for Managing Trabeculectomy Flap- Related Over-Filtration Due to Unavailability of Scleral Patch Graft during Nation-Wide Lockdown

Abstract: Scleral flap tears during trabeculectomy are difficult to repair in a predictable fashion. Donor scleral flap reinforcements are commonly preferred for managing trabeculectomy flap-related over-filtration, leading to shallow anterior chamber (AC). Due to the advent of COVID-19 lockdown, especially in the initial phases, eye banking activities almost came to a standstill, with almost no corneal and/or scleral tissue retrievals. Hence, in this manuscript we have presented a mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Studies have shown that the use of Ologen ® implant produces comparable IOP reduction with trabeculectomy and a lower risk profile when compared to the use of antimetabolites. [ 12 13 14 15 16 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the use of Ologen ® implant produces comparable IOP reduction with trabeculectomy and a lower risk profile when compared to the use of antimetabolites. [ 12 13 14 15 16 17 ]…”
Section: Discussionmentioning
confidence: 99%